A novel approach to the data center hybrid cooling design with containment. (4th March 2017) - Fouladi, Kamran; Schaadt, Joseph; Wemhoff, Aaron P.
ABSTRACT: Hybrid cooling solutions, which consist of the installation of heat exchangers near IT equipment, aim to eliminate hot spots in data centers containing high-density computer cabinets. In addition, cold aisle containment is often used to reduce hot air recirculation to improve energy efficiency. However, the viability and efficiency of each hybrid cooling strategy with or without containment depend on the IT load and equipment arrangement, and no formal procedure exists for selecting the most efficient strategy for a given application. Therefore, this study provides a computational approach for ranking the performance of different cooling strategies based on their capacity and cooling efficiency. The results of analyses indicate that applying containment is beneficial in (1) lowering the maximum temperature of the air entering the racks as airflow rates are increased, and (2) increasing the uniformity of rack inlet temperatures. However, applying containment also requires additional mechanical work by the computer room air handler (CRAH) fan, which may raise the data center power usage effectiveness (PUE). Application of the computational approach discussed here highlights the use of hybrid cooling to lower PUE by reducing the CRAH fan power.